Response of Potato (Solanum tuberosum L.) under Different Levels of Irrigation and Fertigation through Drip System - Serhat Ayas (Turkish Journal of Agriculture: Food Science and Technology)
There are very few studies on cabbage at different fertigation levels in the Marmara Region, where this study was conducted. In this respect, our study has a unique quality. This study was carried out in Bursa Uludag University Yenisehir İbrahim Orhan Vocational School application greenhouses in 2014-2015 years. Five different irrigation treatments (T1: 100% (full irrigation), T2: 75%, T3: 50%, T4: 25%, T5: 0% (non-irrigated)) and two different fertigation treatments; F1.0: 100% (100:100:100 NPK) fertigation and F0.5: 50% (50:50:50 NPK) fertigation were combined together to determine the effects on yield and quality parameters of potatoes. The amount of irrigation water in 2014 and 2015 years varied between 0.0-630.0 mm and 0.0-660 mm, respectively, while evapotranspiration values varied between 180.0-670 mm and 190.0-675 mm, respectively. It was determined that irrigation water and fertigation levels, yield and quality parameters of potatoes were affected significantly. In both application years, the highest yield was obtained from T1F1.0 treatment as 45.0 and 47.0 tons’ ha-1 respectively, while the lowest yield was obtained from T5F1.0 treatment as 4.0 and 5.0 tons ha-1, respectively. In 2014 and 2015 years the crop response factor (ky) values of potato were calculated as 1.11-1.11 and 1.21-1.14, respectively. When the full fertigation (F1.0: 100% -100:100:100 NPK) and the insufficient F0.5: 50% - (50:50:50 NPK) fertigation treatments are compared, significant differences have arisen in terms of yield and quality parameters. T2F1.0 and T2F0.5 treatments can be recommended as the most effective irrigation and fertilization levels of potato.